Keberhasilan Terapi Konservatif pada Persalinan Preterm Disertai dan Tanpa Disertai Ketuban Pecah Dini di RSD dr. Soebandi, Jember - Nurul Furqooniyah; Yonas Hadisubroto; Bagus Hermansyah (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Preterm delivery is the greatest cause of neonatal morbidity and mortality. Preterm delivery can be accompanied by premature rupture of membranes. Preterm delivery with and without premature rupture of membranes are managed by conservative therapy to delay birth. Rupture of membranes causes inadequate protection of the fetus. This study aimed to determine the success of conservative therapy in preterm delivery with and without premature rupture of membranes at Regional Hospital (RSD) dr. Soebandi Jember. The study used secondary data from medical records of pregnant women with spontaneous single preterm delivery that has been given conservative treatment from January 2015-January 2017 period. As many as 149 samples were included for the study, which is collected using total sampling technique. This research used cross sectional research design. Chi-Square statistical test results showed a significance of (p = 0.001 <0.05). It can be concluded that there was a significant difference of the success of conservative therapy between the preterm delivery with and without premature rupture of membranes.